Metastable aluminium atoms floating on the surface of helium nanodroplets - Jeffs, Jay; Besley, Nicholas A.; Stace, Anthony J.; Sarma, Gautam; Cunningham, Ethan M.; Boatwright, Adrian; Wang, Shengfu; Ellis, Andrew M. (American Physical Society, 2015)
Metal atoms have proved to be sensitive probes of the properties of superfluid helium nanodroplets. To date, all experiments on the doping of helium droplets have concentrated on the attachment of metal atoms in their ground electronic states. Here we report the first examples of metal atoms in excited states becoming attached to helium nanodroplets. The atoms in question are aluminium and they have been generated by laser ablation in a metastable quartet state, which attaches to and remains on the surface of helium droplets. Evidence for a surface location comes from electronic spectra, which consist of very narrow absorption profiles that show very small spectral shifts. Supporting ab initio calculations show there to be an energy incentive for a metastable Al atom to remain on the surface of a helium droplet rather than move to the interior. The results suggest that helium droplets may provide a method for the capture and transport of metastable excited atomic and molecular species.